AB0 Blood Groups and Coronary Heart Disease (CHD) - Erikssen, Jan; Thaulow, Erik; Stormorken, Helge; Brendemoen, Ole; Hellem, Arvid (Thrombosis and Haemostasis, 1980)
The view based on epidemiological and laboratory data that blood group A subjects (=A) have clinically significant higher thrombotic potential than blood group 0 subjects (= O), is supported by the present finding of a significantly higher platelet retention in A than 0.The completely normal ABO distribution found among 71 cases of proven latent CHD, and the disproportionate excess of 0 vs. A in a consecutive series of 191 coronary artery bypass candidates apparently conflict with epidemiological data indicating a higher risk of achieving CHD in A than 0. The conflict may be solved by suggestinga) that the »thrombotic proneness« in A compared with 0 causes a poorer prognosis in CHD among the former, leaving a disproportionate excess of 0 among longterm CHD survivors, and b) that AB0-related factors have had an insignificant, independent impact on the evolution of preclinical coronary artery disease in our 71 men with latent CHD.
Keywords: AB0-related coronary risk factors; Platelet retention; Coagulation factors; Blood group A and arterial thrombosis